2019
DOI: 10.1002/cplu.201800658
|View full text |Cite
|
Sign up to set email alerts
|

High‐Spin Mononuclear Iron(III) Complexes with Pentadentate Schiff Base Ligands: Structural Analysis and Magnetic Properties

Abstract: Various substituted 2-hydroxybenzophenones were combined with aliphatic linear triamines to form pentadentate Schiff base ligands. Twelve new iron(III) complexes with the general formula [Fe(L n )X].mCH 3 CN (n = 1-10; X = N 3 À , NCS À or NCSe À ; m = 0-2) have been synthesized, and spectrally as well as structurally characterized. The structural analysis revealed a notable dependence of coordination polyhedra deformation as well as the spatial configuration of donor atoms on the length and symmetry of the Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Complex 2, however, showed low-intensity bands in the range of 550-700 nm due to its expected d-d transitions. 1 H NMR spectra of the H 2 L ligand and its zinc complex were recorded at 298 K in DMSO-d 6 (Figures S1 and S2). In the 1 H NMR spectrum of the ligand, the protons' broad peaks of phenolic OH 8 and OH 6 moieties were observed at 12.9 and 10.8 ppm, respectively.…”
Section: Electronic Absorption Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…Complex 2, however, showed low-intensity bands in the range of 550-700 nm due to its expected d-d transitions. 1 H NMR spectra of the H 2 L ligand and its zinc complex were recorded at 298 K in DMSO-d 6 (Figures S1 and S2). In the 1 H NMR spectrum of the ligand, the protons' broad peaks of phenolic OH 8 and OH 6 moieties were observed at 12.9 and 10.8 ppm, respectively.…”
Section: Electronic Absorption Spectramentioning
confidence: 99%
“…Schiff base ligands are prepared easily and can be readily modified, both electronically and sterically . Schiff base ligands contain multiple potential donor sites, which allow them to bind metal ions with diverse coordination geometries such as bidentate and tridentate . Tetradentate Schiff base ligands also provide a suitable coordination platform for metal ions to provide diverse metallic complexes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This affects the cooperativeness of the complex when SCO occurs, resulting in all complexes exhibiting a permanent HS state. [30] In this work, the pentadentate Schiff base ligands have been chemically modified with methyl and methoxy groups to obtain three complexes with different SCO behaviour. The magnetic properties indicated that when the H atom of the amino nitrogen was substituted by an electron-donating methyl group, the SCO temperature of the complex would move to a lower temperature.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…However, One advantage of using pentadentate Schiff base ligands to synthesize SCO compounds is that auxiliary ligands or bridging ligands can be used to replace the sixth unstable coordination site to achieve fine regulation of SCO complexes. [28][29][30] For example, Matsumoto's group synthesized SCO complexes [Fe III (4-NH 2 py)L]BPh 4 , (4-NH 2 py = 4-aminopyridine; L = pentadentate Schiff base ligand) to study the effect of one-dimensional chain structure composed of hydrogen bonds on the steepness of SCO. [31] Subsequently Xu et al synthesized complexes [Fe(L)(py)] and [Fe(L)(dmap)](BPh 4 ) (L = N,N'-bis(2-hydroxybenzyliden)-1,7-diamino-4-azaheptane; dmap = 4-dimethylaminopyridine) using pentadentate Schiff base ligands and pyridine like ligands.…”
Section: Introductionmentioning
confidence: 99%